Evaluation method for autonomous communication and networking capability of UAV - Haitao ZHAO; Shishun GAO; Haijun WANG; Ting YONG; Jibo WEI (Tongxin xuebao, 2020)
In order to accurately evaluate the autonomous communication and networking capability of these unmanned system which was instructive to the intelligent collaboration of UAV (unmanned aerial vehicle) system,the research of the UAV system which was adapted to the complex environment with countermeasure possibilities was focused on.The autonomous communication and networking capability of UAV system and their relationship from multiple perspectives was analyzed and modeled,including self-adaptation,self-decision,man-UAV interaction,cyber-physical integration and evolution,and an example was provided to illustrate the detailed evaluation process.The example results show that the proposed method comprehensively consider all the key aspects of the performance evaluation,which can be used to quantitatively evaluate the autonomous communication and networking capability of different UAVs or other unmanned systems.